PENILAIAN DIVESTASI SAHAM MERCHISTON GROUP LIMITED PADA PT HOTEL SAHID JAYA INTERNATIONAL TBK - , Dwi Pudyastuti, Ir. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to determine the estimation of the intrinsic value of PT Hotel Sahid Jaya International Tbk. share, when the divestment occurs, by using both discounted cash flow method and relative valuation method. This research also used data of PT Hotel Sahid Jaya International Tbk. financial statement during the last five years from 2005 until 2009. Analysis by using the discounted cash flow method is conducted by several procedures included sales or earnings projection analysis, financial statement projection, free cash flow projection, discount rate determination and value estimation. Analysis by using relative valuation is started by searching any similar companies in the same field of industry after choosing an appropriate ratio or multiples from those companies. This multiples, used to convert a relevant book value variable from PT Hotel Sahid Jaya International Tbk., become an estimation of market value. Multiples or ratio which used were: PER (Price Earning Ratio), PBV (Price to Book Value) and P / S (Price to Sales Ratio). The result from the research that use the discounted cash flow method obtained an intrinsic value estimation of PT Hotel Sahid Jaya International Tbk. share per 2010 equal to Rp1.494,-. The result by using relative valuation obtained the following result: for the estimation of stocks price per share PT Hotel Sahid Jaya International Tbk. by using PER equal to Rp1.112,-, using PBV ratio equal to Rp230,- and using price to sales ratio equal to Rp3.051,-. The mean from this three method equal to Rp1.464,-. Based on this both approaches, the price of PT Hotel Sahid Jaya International Tbk. share at this time is possibility undervalued.